2008
DOI: 10.3341/kjo.2008.22.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Rectus Muscles Transposition in Large Exotropia with Medial Rectus Muscle Transection Following Endoscopic Sinus Surgery

Abstract: PurposeTo evaluate the effect of transposition procedures on the vertical rectus muscle (VRM) in the patients who underwent a medial rectus muscle (MR) transection after endoscopic sinus surgery (ESS).MethodsIn 4 patients with exotropia (XT) and a lack of adduction after ESS, orbital CT or MRI revealed a complete transection of the midportion of the MR. Full-tendon VRM transposition was performed within 3 months after injury (early surgery) in 2 patients with 40Δ XT. Two patients with 70Δ and 85Δ XT underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Repair of the medial orbital wall usually cannot prevent secondary scar formation. [ 11 , 17 , 18 ] In our experience, recovery of the medial rectus was abandoned in 2 cases where severe entrapment and/or adhesion were present and strabismus surgery was employed in these cases. Two of the 27 cases in our study had their medial wall defect repaired through a transconjunctival orbitotomy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Repair of the medial orbital wall usually cannot prevent secondary scar formation. [ 11 , 17 , 18 ] In our experience, recovery of the medial rectus was abandoned in 2 cases where severe entrapment and/or adhesion were present and strabismus surgery was employed in these cases. Two of the 27 cases in our study had their medial wall defect repaired through a transconjunctival orbitotomy.…”
Section: Discussionmentioning
confidence: 97%
“…The range of adduction deficits were recorded at the version test using the following scales: 0 indicated full adduction – free arrival of medial limbus at the medial canthal area, −4 indicates that the medial limbus could not past midline, and −1, −2, and −3 indicated that the eye could rotate nasally from the midline to 75%, 50%, and 25% of full adduction, respectively. [ 11 ] A forced duction test and a forced generation test using toothed forceps were performed to determine restriction or paresis of the affected muscle. If the globe could not be passively rotated further than the patient's effort, restriction was diagnosed; if passive rotation was possible, paresis was diagnosed.…”
Section: Methodsmentioning
confidence: 99%
“…All patients underwent an augmented Hummelsheim procedure (3) or X-type transposition (9) with modifications as documented in Supplemental Digital Content 1 (see Supplemental Table 1 , http://links.lww.com/WNO/A516). Supplemental Digital Content 2 (see supplemental methods, http://links.lww.com/WNO/A515 for more details).…”
Section: Methodsmentioning
confidence: 99%
“…Posterior muscle union combined with posterior scleral fixation sutures has been shown to augment the transposition effect by increasing the tonic contractile forces generated by the muscles and by redirecting the vector forces of the muscle so that they are more parallel to the action of the paralyzed muscle (7). To further increase the tonic forces of the transposed muscle segments, Brooks et al proposed concurrent resection of the transposed segment (8), whereas Cho et al found success with an X-type augmentation in which the transposed muscles are crossed under the paralytic muscle (9).…”
mentioning
confidence: 99%
“…Treatments may require neurosurgical intervention as well as strabismus surgery, depending on the visual acuity of the patients, the cause of their ONP, the angle of deviation, and the presence of amblyopia [ 6 ]. Although appropriate surgical procedures can be rewarding for ONP patients [ 7 9 ], the long-term outcomes between different surgical options showed no statistically significant difference [ 10 ]. Therefore, further insight into ONP is urgently needed for better evaluation and management of ONP.…”
Section: Introductionmentioning
confidence: 99%